River water quality variability in the young volcanic areas in Java, Indonesia - Heru Hendrayana; Indra Agus Riyanto; Azmin Nuha (Journal of Degraded and Mining Lands Management, 2023)
Rivers on Java Island are one of the water supply sources to meet the surrounding population's water needs. However, only large, high-priority rivers underwent a comprehensive water quality assessment. Rivers that aren't a priority are rarely examined, such as sub-watersheds in Kuntulan, Rejoso. Upper Serayu, Gajahwong, and Glondong. The surrounding community utilizes these five watersheds for irrigation, industry, and domestic. Hence, analyzing the water quality index in the five watersheds during the dry season is necessary. The method used in this research is a comparison of the water quality results between the standards of the Indonesian government and WHO, as well as a comparison of the Water Quality Index (WQI) and Pollution Index (PIj). The method often used in Indonesia is PIj, while WQI is more global and hardly used. The difference in the two ways is expected to provide variations in the water quality index. The water quality parameters were pH, TDS, TSS, COD, PO43-, NO3-, Total Coliform, Temperature, and EC. Comparing water quality with water quality standards in the five watersheds shows that several samples exceed the standard. WQI result shows that all river water in the five watersheds belongs to the excellent classification. A different result from the PIj index shows that the five watersheds were dominantly moderately polluted, with several samples considered polluted and extremely polluted. Differences in the index formula and water quality standards cause these different results. The results of the analysis show that the PIj index is more representative than the WQI as the PIj index shows the suitability of the classification comparison of water quality values with water quality standards compared to WQI.